Costs of mental health care resource use in people with obesity: A systematic review - Nienke de Graef; Arianna Morris Gouveia; Aggie Paulus; Inge van der Putten; Emma Frew; Irina Pokhilenko (PLoS ONE, 2025)
Introduction Obesity is a complex condition with significant economic implications. Healthcare costs associated with obesity are spread across all categories of health services, including mental health care. However, little evidence is available regarding the magnitude and types of costs associated with mental health care resource use by people with obesity. Objectives This systematic review aimed to synthesise the evidence on the costs of mental health care resource use by people with obesity. Methods A systematic literature search was conducted in PubMed (Medline), Embase (Ovid), PsycINFO (EBSCO), and Econlit (EBSCO) based on PRISMA guidelines to identify cost-of-illness (COI) studies of obesity published in English since 2016. Peer-reviewed studies estimating obesity-related costs using primary or secondary data in children or adults were included. The COI studies quality tool by Schnitzler et al. was adopted to assess the methodological quality of studies. Data extracted included general study characteristics and costs associated with mental health care. Results were synthesised narratively. Results A total of 5,565 records were identified post-duplication removal. Following selection, 33 COI studies were included, which mentioned mental health care costs; fifteen considered the monetary value of mental health care costs as separate costs in their analyses. The proportion of total annual healthcare costs attributable to mental health care ranged between 0.70% and 25.10%. Discussion Our findings suggest that people with obesity incur substantial costs related to the use of mental health care, yet less than half of the included COI studies reported mental health care costs separately from total healthcare costs attributable to obesity. This highlights the importance of greater transparency and granularity when reporting costs. Furthermore, it is imperative to shed more light on the economic impact of co-morbid obesity and mental health. This research is essential for facilitating effective resource allocation and addressing the healthcare needs of this population.